Exams Washback and Academic Achievement in Mathematics: Investigating from Students’ Perspective at Secondary School Level - Awan, Khurshid Hassan (JSE, 2025)
The study was quantitative in nature and aimed to see the sights about washback of the final exams and its effects on students’ academic achievements. Washback is about the consequences, influences or impacts of final examinations on learning as well as on the teaching process. Therefore, key objective of this investigation was to sightsee students about important effects caused by final examination on their academic achievements at Azad Jammu and Kashmir. The population as a Target of the investigation was all the learners of Mathematics at secondary school level in district Jhelum Valley. As this was a quantitative study, quantitative data analysis techniques were adopted. Tool in the form of a questionnaire as 35Likert scale items with 8 sub items were used to collect the data. The questionnaire aimed at measuring the students’ perceptions regarding Washback of final exams along with its effects on academic achievements in terms affect Resided final exams washback, classroom exams (formative assessment)resided washback, learning strategies resided final exams washback, extra material resided final exams washback, washback techniques resided final exams washback, text book resided final exams washback, curriculum resided final exams washback, time resided final exams washback, Final exams washback as a factor of innovation and some students’ factors. The findings of the research revealed that washback of final exams had very strong level of effects on perceptions of Mathematics students. The findings also pointed out that various student[1]related factors, alongside the domains of the washback, contributed to its increased complexity.